A novel sn-1, 3 specific lipase from Janibacter sp. as catalysts for the high-yield synthesis of long-medium-long type structured triacylglycerols. (1st January 2022) - Cui, Ruiguo; Xu, Long; Lan, Dongming; Yang, Bo; Wang, Yonghua
Highlights: Our novel sn -1, 3 specific lipase MAJ1 enabled high-yield synthesis of LML-type TAGs. The positional specificity index value of lipase MAJ1 reached 96.6. Lipase MAJ1 exhibited a lower optimal temperature than other sn -1, 3 specific lipases. The thermal stability of lipase MAJ1 improved significantly after immobilization. The TAG positional isomers were qualified and quantified by MDMS-SL. Abstract: Our study offers a novel sn -1, 3 specific lipase MAJ1 from marine member Janibacter sp. strain HTCC2649 for preparing long-medium-long (LML) type structured triacylglycerols (TAGs). Firstly, the resin ECR1030 was selected as a suitable support for the immobilization of lipase MAJ1. An efficient synthesis of LML-type structured TAGs by the immobilized lipase MAJ1-catalyzed interesterification of methyl palmitate and tricaprylin was studied in a solvent-free system. The reaction conditions, including substrate molar ratio, temperature and enzyme loading, were optimized. Under the optimum conditions (immobilized lipase MAJ1 of 45 U/g, substrate molar ratio of 4:1, temperature of 35 °C, reaction time of 24 h), the structured TAGs with double long chains (DLCST) were obtained in a yield of 44.3 mol%. Secondly, multi-dimensional mass spectrometry-based shotgun lipidomics (MDMS-SL) was employed to quantify each TAG positional isomer in DLCST. The content of 1, 3-dipalmitoyl-2-capryloyl- sn -glycerol in DLCST was 97.6% determined by the MDMS-SL technology.